Gamma-Rays From Large-Scale Outflows In Starburst Galaxies - Romero, Gustavo Esteban (2020)
The combined effects of supernova explosions and stellar winds produce a hot bubble in thecentral regions of starburst galaxies. As the bubble expands, it can outbreak into the galactichalo driving a superwind that transports hot gas and fields to the intergalactic space. We presentestimates of cosmic ray generation and gamma-ray emission in both this large-scale wind and thebow shocks created around the embedded clouds.